The role of competency improvement of accrual-based financial management report on the preparation of local government financial report - Raden Yudhy Pradityo Setiadiputra (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2019)
Local governments in Indonesia based on the applied rules have the obligation to prepare activity implementation reports, one of which is the Local Government Financial Statements. The Indonesian government is currently implementing accrual-based government financial report. However, in the application of accrual-based government financial report there are still many obstacles experienced by the local governments. The implementation of accrual-based financial report is one form of government bureaucracy reform in the field of financial. In 2005, the central government has issued Government Regulation No. 24 year 2005 on Government Accounting Standards (SAP) which regulates the recognition of revenues and expenditures using the cash basis, while for assets, liabilities and equity using the accrual basis. The regulation has been changed to Government Regulation No. 71 year 2010 which enacts accrual-based SAP for both income, expenditure, assets, liabilities and equity by 2015. The central government has devised a strategic step to implement the accrual basis. In order to support the implementation of the accrual basis accounting application, it is necessary to align the competence of the stakeholder employees in the preparation of local government financial statements, considering that the local government financial statements is a benchmark in assessing the performance of the local governments by the central government. The alignment of competence can be done by implementation of competence improvement such as performing training education, technical guidance, socialization and the formation of community of practices.